Reversible Jackhammer esophagus in a patient with a gastric band. Issue 4 (7th March 2019) - Woo, Matthew; Andrews, Christopher N.; Buresi, Michelle
Abstract : We wish to report a case of Jackhammer esophagus in a patient with laparoscopic gastric band, with confirmed resolution of hypertensive peristalsis on deflation of the band. This finding adds to the growing body of evidence that outlet obstruction plays an important role in the pathophysiology of Jackhammer esophagus, which remains incompletely defined.